Labour Supply and Demand, Absenteeism, and Union Behaviour - Reza, Ali M. (Review of Economic Studies, 1975)
Journal Article Labour Supply and Demand, Absenteeism, and Union Behaviourh Get access Ali M. Reza Ali M. Reza University of Pittsburgh Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 42, Issue 2, April 1975, Pages 237–247, https://doi.org/10.2307/2296531 Published: 01 April 1975